From metaphor machine to being with apparatus - Feinstein, K. * (Revista do Programa de Pós-graduação em Arte, 2020)
This paper takes a look at how we have developed devices to create and transmit meaning. It looks at how these devices have been designed and used to present a view of the world to the viewer. It also looks at what the tendencies within the functioning of media devices are and how that changes the way we perceive information and create world views. Furthermore, it asks how the nature of these devices determine how we communicate through them and what are the tensions they create. Lastly, we ask what this means for present and future use of such technology in an experiential and informative environment.